Struktur Komunitas Makroalga Di Perairan Tenggara Pulau Serangan, Bali - Ni Luh Putu Ayu Sumarni; I Wayan Gede Astawa Karang; Widiastuti Karim (Journal of Marine Research and Technology, 2019)
Macroalgae is one of the biota that is found in all Indonesian waters. Macroalgae has an important role in marine ecosystems, namely as producers, ingredients and pharmacy. The purpose of this research was to determine the community structure of macroalgae. The community structures were measured by using a square transect of 1x1 m2 within a 50 m2 squared transect. Thus macroalgae were determined for its density, diversity, biomass and distribution. The differences among community structures at each station were analyzed by using the One-way Anova. The results showed that the macroalgae were classified into red, brown and green macroalgae. The highest macroalgae density wasw 21 ind/m2 and the lowest was 8 ind/m2. The diversity of macroalgae was in the medium category which the most dominant was red macroalgae. It is likely due to different ability to get the nutrients among macroalgae. The highest biomass was found in the red macroalgae while the lowest was in the green macroalgae. It might be related to the large size and weight of the thallus of red macroalgae. The One-way Anova analysis showed that there was a significant difference in macroalgae density and biomass at each station.